Computed tomographic measurements with and without myelography to characterise thoracolumbar extruded disc herniation. (4th September 2013) - Buttin, P.; Millet, M.; Cousin, S.; Carozzo, C.; Cachon, T.; Fau, D.; Chuzel, T.; Viguier, E.
Abstract : OBJECTIVE: To determine association between computed tomography measurements of spinal cord compression and postoperative outcome . METHODS: A retrospective review of medical records of dogs presenting with intervertebral disease. Data were collected with a minimum of 2 years follow‐up period. Computed tomography morphometric indices, particularly the ratio of spinal cord or herniated disc to vertebral canal dimensions, were obtained from survey and myelogram computed tomographic images. The pattern of disc disease was scored as single or continuous (multiple herniated discs), and was compared to postoperative outcome . RESULTS: Fifty‐two dogs were included. There was no significant correlation between the degree of spinal cord compression and postoperative outcome. However, postoperative outcome differed significantly between dogs with single or continuous patterns of disc disease (P=0·001). Of those with single patterns, 75% had a postoperative outcome score greater than 75% while 75% of continuous pattern cases had scores lower than 83% . CLINICAL SIGNIFICANCE: Simple observation of the pattern of disc disease as revealed by computed tomography could be used as a prognostic indicator. The outcome tends to be better for single patterns of disc disease, whereas the outcome was poor for most cases with continuous patterns .